Engineering elastic properties into an anti-TNFα monoclonal antibody. Issue 1 (1st January 2018) - Sadhukhan, Ramkrishna; Brown, Nathan; Ouellette, David; Banach, David; Filoti, Dana I.; Winarta, David; Raghavendra, Reema; Sousa, Silvino; Darcy, Anhdao; Alessandri, Leslie; Ivanov, Alexander; Bose, Sahana; et al.
Abstract: Injecting anti-tumor necrosis factor (TNF)α antibodies into patient joints at the site of inflammation, inter-articular (IA) delivery, has demonstrated modest success for treatment of Spondyloarthritis (SpA), Rheumatoid Arthritis (RA), and osteoarthritis. However, IA delivery is not the treatment route of choice due to rapid clearance from the site of administration. Elastin-like polypeptides (ELPs) are reported to undergo phase transition; forming reversible aggregates above their transition temperature, which when injected into IA space have a 25-fold longer half-life compared to the soluble form. Here, we fused an ELP repeat to the C-terminus of each heavy chain of an anti-TNFα monoclonal antibody (mAb) and provide detailed characterization of the fusion IgG molecule. Expression and purification yielded homogenous protein confirmed by gels, hydrophobic-interaction chromatography, Capilary Electrophoresis (CE), Mass Spectrometry (MS), and analytical ultracentrifugation. The ELPs altered hydrophobicity and pI of the parent mAb and new elastic properties were imparted to the molecule; forming large stable complexes with a hydrodynamic radius of 40 nm above 39°C that dissociated into soluble, active monomer below 37°C. The fusion mAb retained its affinity and ability to neutralize TNFα as determined by surface plasmon resonance and cell-based assay, respectively, with equal potency to unmodified anti-TNFα mAb. Differential-scanning calorimetry studies show stabilization of adjacent CH 2 and CH 3 domains in the fusion molecule and the aggregated molecule was found to be fully functional after 7 days at 37°C. For the first time, we reveal architecture of an ELP-fusion mAb and binding to antigen using single-particle-transmission-electron microscopy. Unstructured ELP was visualized at the C-terminus and binding to antigen was shown at the N -terminus. Collectively, these studies indicate that it is possible to impart elastic properties to a monoclonal antibody while retaining purity, stability, and ability to effectively bind and neutralize antigen.